A Comparative Study of Coronary Angiographic Data between Diabetic and Non-Diabetic Patients with Acute Coronary Syndrome (University Heart Journal, 2019)
Introduction: Cardiovascular diseases is a major health burden in developing countries like Bangladesh. Patients with acute coronary syndrome(ACS) are at risk for death, myocardial infarction or recurrent ischaemic events. Comorbidity like DM plays a significant role in the outcome of such patients. So the objective of the present study was to see the coronoary angiographic(CAG) findings among diabetic and nondiabetic patients in our context. Methods: Patients presenting with the symptoms of ACS in the Department of Cardiology in a tertiary care center were selected for ECG and cardiac troponin 1. Then according to the defined criteria they was selected for the study. These patients were followed up to their hospital stay period. History of the patient, physical examination and necessary investigations was done. ACS patients were divided into two groups. 1. ACS with DM and 2. ACS without DM. CAG was done among those patients with ACS. Finally CAG findings in two groups were compared systematically. Data were analyzed by SPSS 20. Results: Among the 200 patients total male were 80.5% and total female were 19.5%). Male to female ratio was 5:1. Regarding age distribution it was found matched in both groups. Most patients were at age group 41-50 and 51-60 years which was 31% and 45% respectively. Regarding presence of hypertension in both groups, diabetic group had more hypertensive patients(81%) than the nondiabetic(71%) group (p-0.098). Regarding analysis of CAG findings in diabetic and non diabetic groups LMCA involvement was 16% and 12%, LAD 32% and 28%, LCX 22% and 23%, RCA 23% and 20% and triple vessel was 15% and 14% respectively. Only 5(2.5%) patients were found not to having any lesion. Conclusions: ACS with or without DM has variable CAG findings. So special care should be taken when dealing with such cases.University Heart Journal Vol. 15, No. 1, Jan 2019; 34-36